Age-Related Deficits in Electrophysiological and Behavioral Measures of Binaural Temporal Processing - Koerner, Tess K.; Muralimanohar, Ramesh Kumar; Gallun, Frederick J.; Billings, Curtis J. (Frontiers in Neuroscience, 2020)
Binaural processing, particularly the processing of interaural phase differences, is important for sound localization and speech understanding in background noise. Age has been shown to impact the neural encoding and perception of these binaural temporal cues even in individuals with clinically normal hearing sensitivity. This work used a new electrophysiological response, called the interaural phase modulation-following response (IPM-FR), to examine the effects of age on the neural encoding of interaural phase difference cues. Relationships between neural recordings and performance on several behavioral measures of binaural processing were used to determine whether the IPM-FR is predictive of interaural phase difference sensitivity and functional speech understanding deficits. Behavioral binaural frequency modulation detection thresholds were measured to assess sensitivity to interaural phase differences while spatial release-from-masking thresholds were used to assess speech understanding abilities in spatialized noise. Thirty adults between the ages of 35 to 74 years with normal low-frequency hearing thresholds were used in this study. Data showed that older participants had weaker neural responses to the interaural phase difference cue and were less able to take advantage of binaural cues for speech understanding compared to younger participants. Results also showed that the IPM-FR was predictive of performance on the binaural frequency modulation detection task, but not on the spatial release-from-masking task after accounting the effects of age. These results confirm previous work that showed that the IPM-FR reflects age-related declines in binaural temporal processing and provide further evidence that this response may represent a useful objective tool for assessing binaural function. However, further research is needed to understand how the IPM-FR is related to speech understanding abilities.